2020
DOI: 10.1590/1413-812320202510.34312018
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre sentido de coherencia y diabetes mellitus: una revisión sistemática

Abstract: Resumen El objetivo fue sintetizar las mejores evidencias científicas sobre el efecto del sentido de coherencia en el desarrollo de la enfermedad, tratamiento e indicadores biomédicos de control metabólico y desarrollo de complicaciones de personas en riesgo de desarrollar diabetes y en diabéticos. El método utilizado fue la revisión sistemática. Búsqueda y selección por dos revisores independientes en las bases de datos Scopus, Web of Science, PubMed, Ebsco, Science Direct y manuales, disponibles hasta 2017, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
1
2
0
5
Order By: Relevance
“…Additionally, for the inner resilience and coherence scores (ICS subscale 1), significantly better ICS resilience scores for long-term oncology survivors compared to healthy controls and long-term diabetes patients were found; and the superiority of short-term diabetes patients compared to long-term diabetes patients was found. These results are in line with a study by Márquez-Palacios et al (2020), indicating that coherence (measured in this study as SOC) has a strong correlation with diabetes in different phases of the disease [ 62 ]. Additionally, SOC seems to be a protective factor for demoralization regarding women with a recent gynecological cancer diagnoses [ 11 , 63 ], and long-term cancer survivors with high SOC, in which a strong SOC predicted survival in a Hawaiian sample [ 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, for the inner resilience and coherence scores (ICS subscale 1), significantly better ICS resilience scores for long-term oncology survivors compared to healthy controls and long-term diabetes patients were found; and the superiority of short-term diabetes patients compared to long-term diabetes patients was found. These results are in line with a study by Márquez-Palacios et al (2020), indicating that coherence (measured in this study as SOC) has a strong correlation with diabetes in different phases of the disease [ 62 ]. Additionally, SOC seems to be a protective factor for demoralization regarding women with a recent gynecological cancer diagnoses [ 11 , 63 ], and long-term cancer survivors with high SOC, in which a strong SOC predicted survival in a Hawaiian sample [ 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…En esta investigación fueron tomados en cuenta diversos aspectos metodológicos señalados en investigaciones previas (35) que podrían sesgar los resultados. Para evitar este sesgo, se atendieron las siguientes recomendaciones: la más importante fue que la medición del SOC y los biomarcadores se haga en un corto periodo de tiempo (máximo 7 días).…”
Section: Discussionunclassified
“…Las fortalezas de esta investigación fueron evaluar el SOC y la HbA1c con menos de siete días de diferencia entre ambas mediciones, también incluir en la regresión logística variables que pueden modificar el nivel de HbA1c en los diabéticos y medir el SOC con una versión validada previamente. Todos estos elementos ayudan a tener resultados con más objetividad y reafirman el rol del SOC en el control glucémico después de controlar estos errores metodológicos señalados en estudios anteriores (35) . Las debilidades del estudio son el tamaño de la muestra ya que una muestra más grande hubiera permitido una mayor robustez en el modelo y la técnica del muestreo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Empirical evidence demonstrated that strong SoC is associated with numerous positive health outcomes. In T2DM, a recent systematic review concluded that strong SoC is associated with better glycaemic values and less T2DM-related complications ( Márquez-Palacios et al , 2020 ). However, there is a scientific knowledge gap regarding evaluating salutogenic interventions, particularly regarding salutogenic interventions promoting healthy eating practices ( Mittelmark et al , 2016 ; Langeland et al , 2022b ).…”
Section: Introductionmentioning
confidence: 99%